2002
DOI: 10.1016/s0886-3350(01)01254-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a truncated-edged silicone foldable intraocular lens in Indian eyes

Abstract: The CeeOn Edge 911A IOL was well tolerated in Indian eyes, and the posterior capsule remained clear. Larger patient groups with a longer follow-up will provide more useful information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Intraocular lenses with at least 1 edge that creates a sharp bend in the posterior capsule have become the preferred design, regardless of the IOL material, because of the edge's barrier effect to LECs. [1][2][3][4][5][6][7][8]12,[14][15][16][17][18]23 This design modification can yield dramatic results. In a study of 45 eyes 2 years after surgery, Kruger et al 23 found a 0% PCO rate in eyes with a square-edged silicone IOL but of 43% in eyes with a round-edged silicone IOL made by the same manufacturer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular lenses with at least 1 edge that creates a sharp bend in the posterior capsule have become the preferred design, regardless of the IOL material, because of the edge's barrier effect to LECs. [1][2][3][4][5][6][7][8]12,[14][15][16][17][18]23 This design modification can yield dramatic results. In a study of 45 eyes 2 years after surgery, Kruger et al 23 found a 0% PCO rate in eyes with a square-edged silicone IOL but of 43% in eyes with a round-edged silicone IOL made by the same manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…Nishi and coauthors 13 found that fibrotic fusion of the anterior and posterior capsule edges is essential to the PCO-minimizing effect of a sharp-edged optic. 13 Determining whether a specific IOL leads to a higher or lower PCO rate than another IOL has generally been accomplished through 1 of 3 methods: monitoring groups of patients in whom specific IOLs are implanted [14][15][16][17] ; tracking PCO or Nd:YAG capsulotomies visible in posterior photographs of eye-bank eyes 1,9,18 ; quantifying the late PCO visible in retroillumination photographs of patients' eyes. 12,14,[19][20][21][22] These methods rely on IOLs that have been in wide use 2 to 3 years before the incidence of PCO can be stated reliably.…”
mentioning
confidence: 99%
“…Πρέπει λοιπόν να θυµόµαστε ότι διαφορετικής απόχρωσης ενδοφακοί στον ίδιο ασθενή ίσως να µην είναι αποδεκτοί και να µας οδηγήσουν στην αντικατάσταση του ενδοφακού [92].…”
Section: αλλαγή ενδοφακού λόγω διαφορετικού χρώµατοςunclassified